Opiate Analgesics as Negative Modulators of Adult Hippocampal Neurogenesis: Potential Implications in Clinical Practice - Bortolotto, Valeria; Grilli, Mariagrazia (Frontiers in Pharmacology, 2017)
During the past decade, studies of the mechanisms and functional implications of adult hippocampal neurogenesis (ahNG) have significantly progressed. At present it is proposed that adult born neurons may contribute to a variety of hippocampal-related functions, including specific cognitive aspects and mood regulation. Several groups focussed on the factors that regulate proliferation and fate determination of adult neural stem/progenitor cells (NSC/NPC), including clinically relevant drugs. Opiates were the first drugs shown to negatively impact neurogenesis in the adult mammalian hippocampus. Since that initial report, a vast array of information has been collected on the effect of opiate drugs, by either modulating proliferation of stem/progenitor cells or interfering with differentiation, maturation and survival of adult born neurons. The goal of this review is to critically revise the present state of knowledge on the effect of opiate drugs on the different developmental stages of adult hippocampal neurogenesis, as well as the possible underlying mechanisms. We will also highlight the potential impact of deregulated hippocampal neurogenesis on patients undergoing chronic opiate treatment. Finally, we will discuss the differences in the negative impact on ahNG among clinically relevant opiate drugs, an aspect that may be potentially taken into account to avoid long-term deregulation of neural plasticity and its associated functions in the clinical practice.